Informality and Relations in International Judicial Appointments : Evidence from Sub-regional Courts in Africa - Kisakye, Diana; Stroh, Alexander (The African Review, 2024)
Informality in international judicial selection practices has been acknowledged but rarely systematically researched. Described as “design innovations” that are hard to grasp, national judicial appointments to international courts (ICs), even in the most established democracies, are permeated by opacity and secretiveness that remains puzzling to researchers and the legal complex alike. This article presents evidence from three African sub-regional courts to reify the informal dimension of international judicial appointments. Drawing on qualitative research that employs two country case studies, Uganda and Malawi, we demonstrate how the particularly thin formal selection rules leave much leverage to informalities at various levels of governance. Through interviews and judicial biographical data, we reconstruct judicial appointment practices and their dynamics to account for relevant informalities and relations that shed light on the selection of judges to ICs. We argue that appointment practices are less ad hoc or arbitrary than they often appear but mirror the states’ commitment to regional integration, political assessment of the respective regional organisation, and perceptions of the courts’ relevance and ambitions in relation to the political appointers and selectors. Moreover, we raise new concerns about the risk of more silent and subtle backlash against bold regional courts.